Influence of ultrasonic shot peening on corrosion behavior of 7075 aluminum alloy - Pandey V.; Singh J.K.; Chattopadhyay K.; Srinivas N.C.S.; Singh V. (My University, 2025)
This investigation addresses the effect of surface nanostructure developed through ultrasonic shot peening (USSP) on corrosion behavior of 7075 aluminum alloy. USSP develops surface nanostructure, induces severe plastic deformation, refines grain size up to certain depth and imparts compressive residual stress in the surface region. The sample USSPed for 15 s (USSP 15) exhibited lower current density (0.564 μA/cm2) and higher corrosion potential (−0.695 V) as compared with that of the un-USSP specimen with 1.269 μA/cm2 and -0.839 V respectively. The enhancement in corrosion resistance of USSPed sample is due to rapid development of uniform, homogeneous and effective passive layer on the nano-structured surface coupled with refinement of the coarse precipitates. Also, there is optimum combination of surface roughness, compressive residual stress, and dislocation density in the surface region to produce highest corrosion resistance in the USSP 15 condition. © 2017